Effect and in silico characterization of genetic variants associated with severe spermatogenic disorders in a large Iberian cohort. (20th April 2021) - Cerván‐Martín, Miriam; Bossini‐Castillo, Lara; Rivera‐Egea, Rocío; Garrido, Nicolás; Luján, Saturnino; Romeu, Gema; Santos‐Ribeiro, Samuel; Castilla, José A.; Gonzalvo, María del Carmen; Clavero, Ana; Vicente, Francisco Javier; et al.
Abstract: Background: Severe spermatogenic failure (SpF) represents the most extreme manifestation of male infertility, as it decreases drastically the semen quality leading to either severe oligospermia (SO, <5 million spermatozoa/mL semen) or non‐obstructive azoospermia (NOA, complete lack of spermatozoa in the ejaculate without obstructive causes). Objectives: The main objective of the present study is to analyze in the Iberian population the effect of 6 single‐nucleotide polymorphisms (SNPs) previously associated with NOA in Han Chinese through genome‐wide association studies (GWAS) and to establish their possible functional relevance in the development of specific SpF patterns. Materials and methods: We genotyped 674 Iberian infertile men (including 480 NOA and 194 SO patients) and 1058 matched unaffected controls for the GWAS‐associated variants PRMT6 ‐rs12097821, PEX10 ‐rs2477686, CDC42BPA ‐rs3000811, IL17A ‐rs13206743, ABLIM1 ‐rs7099208, and SOX5 ‐rs10842262. Their association with SpF, SO, NOA, and different NOA phenotypes was evaluated by logistic regression models, and their functional relevance was defined by comprehensive interrogation of public resources. Results: ABLIM1 ‐rs7099208 was associated with SpF under both additive (OR = 0.86, p  = 0.036) and dominant models (OR = 0.78, p  = 0.026). The CDC42BPA ‐rs3000811 minor allele frequency was significantly increased in the subgroup of NOA patients showing maturation arrest (MA) of germ cells compared to the remaining NOA cases under the recessive model (OR = 4.45, p  = 0.044). The PEX10 ‐rs2477686 SNP was associated with a negative testicular sperm extraction (TESE) outcome under the additive model (OR = 1.32, p  = 0.034). The analysis of functional annotations suggested that these variants affect the testis‐specific expression of nearby genes and that lincRNA may play a role in SpF. Conclusions: Our data support the association of three previously reported NOA risk variants in Asians ( ABLIM1 ‐rs7099208, CDC42BPA ‐rs3000811, and PEX10 ‐rs2477686) with different manifestations of SpF in Iberians of European descent, likely by influencing gene expression and lincRNA deregulation.